2018
DOI: 10.1016/j.dib.2018.01.096
|View full text |Cite
|
Sign up to set email alerts
|

Data on a new sensitivity-improved miniaturized label-free electrochemical biosensor

Abstract: This article presents a new sensitivity-improved electrochemical measurement architecture for cardiovascular disease (CVD) diagnosis by detecting CVD biomarkers, S100 beta protein and C-reactive protein (CRP). The new architecture includes a design for a new electrochemical measurement set-up, which improves the reaction conditions of chemical and biological molecules and incorporates a newly biochip design. With the new architecture, electrochemical measurement experiments were undertaken. The results obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…CRP; [101][102][103] EC (bio)sensor conguration typically comprises two main parts: (i) immobilized recognition element providing the selectivity to the target analyte (T) and (ii) the EC transducer serving as a converter of the biorecognition event to an electronic signal. 107,108 The most common transducers reported for mTBI-related biosensors include gold electrodes (disk, microelectrodes, lms and interdigitated electrodes 109,110 ), carbon-based (glassy carbon, carbon paste, carbon nanotubes (CNTs) 111 ) and graphene-based materials. Other approaches have been reported employing conductive polymer (CP) nanowires (NWs), such as polypyrrole (PPy) NWs 112,113 or silica-NWs.…”
Section: Design Of Electrochemical Sensors For Detection Of Protein Biomarkers Relevant To Mtbimentioning
confidence: 99%
“…CRP; [101][102][103] EC (bio)sensor conguration typically comprises two main parts: (i) immobilized recognition element providing the selectivity to the target analyte (T) and (ii) the EC transducer serving as a converter of the biorecognition event to an electronic signal. 107,108 The most common transducers reported for mTBI-related biosensors include gold electrodes (disk, microelectrodes, lms and interdigitated electrodes 109,110 ), carbon-based (glassy carbon, carbon paste, carbon nanotubes (CNTs) 111 ) and graphene-based materials. Other approaches have been reported employing conductive polymer (CP) nanowires (NWs), such as polypyrrole (PPy) NWs 112,113 or silica-NWs.…”
Section: Design Of Electrochemical Sensors For Detection Of Protein Biomarkers Relevant To Mtbimentioning
confidence: 99%
“…The sensor is free from Warburg diffusion limitation, a condition that may arise from micro-structured fabricated electrodes, and is suitable to be incorporated with a potentiostat render for point-of-care testing. Kuo et al [ 70 ] reported an increase of 85.81% in the sensitivity of electrodes with zig-zag structures at the edges. Therefore, optimization of the design and dimensions of the electrode is a crucial step in determining the electrical performances of devices in biosensing applications.…”
Section: Infection-mediated Clinical Biomarkers and Their Electrical Biosensorsmentioning
confidence: 99%